The Effect of Health Promotion Using Booklet Media On The Level of Compliance With Medication In Hypertension Patients - Fadia Auliatus Solehah; Maimum; Vina Neldi (International Journal of Health and Pharmaceutical (IJHP), 2026)
Background: Hypertension is a chronic disease with high prevalence in Indonesia, reaching 34.4%, which increases the risk of cardiovascular complications due to low patient adherence to medication. Limited knowledge, low health literacy, insufficient social support, and cultural beliefs influence adherence behavior. Health promotion using educational media, such as booklets, is considered effective in improving patients' understanding and medication adherence. Objective: To review the scientific evidence on the effect of booklet-based health promotion on medication adherence in hypertensive patients. Methods: This study employed a descriptive literature review with narrative and thematic analysis. Literature searches were conducted in PubMed, Scopus, ScienceDirect, Google Scholar, and SINTA using keywords: hypertension, medication adherence, health promotion, educational booklet, and compliance. Twenty relevant articles published between 2022–2025 were analyzed, including quasi-experimental, randomized controlled trials (RCTs), cross-sectional studies, and systematic reviews. Data were extracted on methods, study subjects, measurement instruments (HK-LS, MMAS-8, MARS), and main outcomes related to knowledge, adherence, self-efficacy, and clinical outcomes. Results: Booklet-based interventions effectively improved patients' knowledge, contributing to increased medication adherence. Interactive, continuous, and culturally tailored educational strategies were more effective than static printed media. Key factors supporting success include health literacy, social support, and patients' perceptions of therapy. Conclusion: Health promotion using booklets is effective in enhancing medication adherence among hypertensive patients, especially when combined with interactive education and ongoing support.